Generation of free radicals by the effect of vitamin C on a ferrous sulfate antianemic syrup - Guija-Guerra, Henry (2018)
Objective: To determine the effect of vitamin C on ferrous sulfate, the active ingredient of an antianemic syrup. Materials and methods: The reaction between the ferrous sulfate contained in an antianemic syrup and vitamin C was determined using the decomposition technique of deoxyribose, which evaluates the formation of malondialdehyde by the action of free radicals. Results: In an assay medium consisting of 50 mM phosphate buffer (pH 7.4), the ferrous sulfate antianemic syrup at a concentration of 1.080 mM reacted with vitamin C at concentrations between 5.0 x 10-6 mM and 0.5 mM, generating levels of free radicals that decrease when vitamin C is used at a concentration of 5.0 x 10-2 mM, and increase at a concentration of 0.5 mM. When ferrous sulfate is used under similar conditions, an increase in the generation of free radicals is observed, which reaches a maximum value with vitamin C at a concentration of 5.0 x 10-6 mM, remains unchanged at concentrations of two orders of magnitude higher, and subsequently decreases at higher concentrations. Vitamin C at a concentration of 1.0 mM reacts with ferrous sulfate used at concentrations between 0.270 and 2.160 mM, describing a hyperbolic curve. In contrast, ferrous sulfate syrup used at the same concentrations showed a high increase at low non-linear concentrations, but a linear response from the 0.540 mM concentration of the syrup, a response that was higher than that reached by the ferrous sulfate dissolved in distilled water. Conclusions: Vitamin C reacts with ferrous sulfate syrup generating free radicals. This response depends on the relative concentrations of ferrous sulfate, vitamin C and syrup excipients.